2023
DOI: 10.1523/jneurosci.0628-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of Behavioral and Cortical Emergence from Isoflurane Anesthesia by GABAergic Neurons in Basal Forebrain

Abstract: General anesthesia shares many similarities with natural sleep in behavior and electroencephalogram (EEG) patterns. The latest evidence suggests that general anesthesia and sleep–wake behavior may share overlapping neural substrates. The GABAergic neurons in the basal forebrain (BF) have recently been demonstrated to play a key role in controlling wakefulness. It was hypothesized that BF GABAergic neurons may participate in the regulation of general anesthesia. Here, usingin vivofiber photometry, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Activation of the basal forebrain GABAergic neurons with chemogenetics and optogenetics decreased sensitivity to isoflurane, prolonged the induction time, and accelerated emergence from isoflurane anesthesia. Optogenetic activation of the basal forebrain GABAergic neurons decreased delta power and the burst suppression ratio during 0.8% and 1.4% isoflurane anesthesia ( Cai et al, 2023 ). In addition, chemogenetic activation of astrocytes in the basal forebrain had a significantly shortened isoflurane induction time, prolonged emergence time, and augmented delta power of EEG during anesthesia maintenance and recovery periods ( Lin et al, 2023 ).…”
Section: Basal Forebrainmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the basal forebrain GABAergic neurons with chemogenetics and optogenetics decreased sensitivity to isoflurane, prolonged the induction time, and accelerated emergence from isoflurane anesthesia. Optogenetic activation of the basal forebrain GABAergic neurons decreased delta power and the burst suppression ratio during 0.8% and 1.4% isoflurane anesthesia ( Cai et al, 2023 ). In addition, chemogenetic activation of astrocytes in the basal forebrain had a significantly shortened isoflurane induction time, prolonged emergence time, and augmented delta power of EEG during anesthesia maintenance and recovery periods ( Lin et al, 2023 ).…”
Section: Basal Forebrainmentioning
confidence: 99%
“…Furthermore, optogenetic activation of the basal forebrain GABAergic terminals in the thalamic reticular nucleus (TRN) also strongly promoted cortical activation and behavioral emergence from isoflurane anesthesia. EEG spectral analysis showed that optogenetic activation induced a notable decline in delta power and theta power, an increase in alpha power and beta power ( Cai et al, 2023 ). Collectively, these results showed that the basal forebrain plays a pivotal role in facilitating behavioral and cortical emergence from general anesthesia.…”
Section: Basal Forebrainmentioning
confidence: 99%
“…25,26,31 Brief optogenetic stimulation of TRN neurons induces spindles in the cortex, 32 whereas the alpha oscillations (8)(9)(10)(11)(12) in the cortex is identified as a characteristic of propofol-induced anesthesia, [33][34][35][36][37] which indicated the involvement of TRN in GA regulation. Furthermore, manipulation of the basal forebrain (BF)-TRN or the locus coeruleus (LC)-TRN pathway affected the progress of isoflurane-or propofol-mediated GA. 38,39 The TRN is anatomically divided into several sectors distributed along the plane of the nucleus, and each sector forms distinct neural circuits which are composed of the specific cortical afferents and the thalamic target of TRN neurons. 40 The anterior sector of the TRN (aTRN) receives the projections from the prefrontal cortex (PFC) 41 and sends mainly outputs to the thalamic nonspecific nuclei, such as the thalamic mediodorsal nucleus (MD) and the VPM 40 to play a part the regulation of the corticothalamic and thalamocortical activities.…”
Section: Introductionmentioning
confidence: 99%
“…Brief optogenetic stimulation of TRN neurons induces spindles in the cortex, 32 whereas the alpha oscillations (8–12 Hz) in the cortex is identified as a characteristic of propofol‐induced anesthesia, 33–37 which indicated the involvement of TRN in GA regulation. Furthermore, manipulation of the basal forebrain (BF)‐TRN or the locus coeruleus (LC)‐TRN pathway affected the progress of isoflurane‐ or propofol‐mediated GA 38,39 . The TRN is anatomically divided into several sectors distributed along the plane of the nucleus, and each sector forms distinct neural circuits which are composed of the specific cortical afferents and the thalamic target of TRN neurons 40 .…”
Section: Introductionmentioning
confidence: 99%